Perancangan sistem promosi produk-produk UMKM berbasis Openchart untuk kesejahteraan masyarakat di daerah Sungai Pua - Putri, Melyana; Zulfikar, Zulfikar; Fadilah, Titi (Yayasan Lembaga Studi Makwa, 2024)
This research aims to address the issue of unstable turnover fluctuations in MSMEs in the Sungai Pua area, which is one of the regions with significant potential for the growth of micro, small, and medium enterprises. (UMKM). As the main drivers of the local economy, MSMEs in this area offer a variety of local products, such as handicrafts, processed food products, and other household items, which have significant potential in the region. However, MSME actors here often face various challenges that hinder the development of their businesses. Limited access to broader markets and a lack of understanding of digital marketing technology are the main issues that slow down business progress. In addition, limited resources, both financially and in terms of labor, make it difficult for MSME actors to manage promotions efficiently. Sales fluctuations that result in unstable revenue pose a significant challenge in maintaining income stability and business sustainability. Dependence on traditional marketing methods that rely solely on direct sales in the local market increasingly reduces the space for SMEs to compete in the rapidly growing market. Therefore, innovative solutions are needed to help MSME actors overcome these limitations and enhance their competitiveness. This study aims to design an OpenCart-based promotional system that can help SMEs market their products more effectively. This system is designed with various features, such as product management, digital promotion, social media integration, and sales reporting, aimed at improving operational efficiency and expanding market access. The Research and Development (R&D) method with a 4D model approach is applied in this study, which includes needs analysis, design, development, implementation, and system functionality evaluation to ensure successful implementation in the context of MSMEs.